2013
DOI: 10.1037/a0029399
|View full text |Cite
|
Sign up to set email alerts
|

Rejected by peers—Attracted to antisocial media content: Rejection-based anger impairs moral judgment among adolescents.

Abstract: Adolescence is an important developmental stage during which both peers and the media have a strong influence. Both peer rejection and the use of morally adverse media are associated with negative developmental outcomes. This study examines processes by which peer rejection might drive adolescents to select antisocial media content by tying together developmental research on peer rejection and research on media effects. Assumed underlying mechanisms are rejection-based anger and frustration and the adolescent'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 61 publications
(82 reference statements)
2
13
0
Order By: Relevance
“…Considering the findings of Study 1, we speculate that violent video games selection in adolescence as a response to social exclusion will further influence beliefs, attitudes, and behavior accordingly, leading to even stronger preferences for violent video games (see also Plaisier & Konijn, ). In turn, violent video games exposure may produce aggression‐related knowledge structures and a hostile expectation bias (Bushman & Anderson, ) which may prime adolescents to interpret ambiguous social situations as hostile, thus fostering hurt feelings and increasing feelings of exclusion.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Considering the findings of Study 1, we speculate that violent video games selection in adolescence as a response to social exclusion will further influence beliefs, attitudes, and behavior accordingly, leading to even stronger preferences for violent video games (see also Plaisier & Konijn, ). In turn, violent video games exposure may produce aggression‐related knowledge structures and a hostile expectation bias (Bushman & Anderson, ) which may prime adolescents to interpret ambiguous social situations as hostile, thus fostering hurt feelings and increasing feelings of exclusion.…”
Section: Discussionmentioning
confidence: 90%
“…Although sometimes socially excluded individuals respond in ways that should facilitate re‐affiliation (e.g., Maner, DeWall, Baumeister, & Schaller, ; Williams & Sommer, ), research found that often exclusion increases a victim's tendency to act aggressively toward the excluders. In line with these evidences, Plaisier and Konijn () showed that, compared to non‐rejected peers, peer‐rejected adolescents reported higher levels of anger and frustration, which were related to more lenient moral judgment of antisocial media contents. In turn, such moral judgment was associated with a greater preference for antisocial YouTube clips.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Therefore, the life risking an attack on the Malala was one of the examples where it was criticized as well and created some doubts. While on the other hand, its positive effect turned the people's anger towards those who attacked the Malala and people started to talk to the Taliban [14]. This shift was seen after the sad incidence of attack on the Malala [15].…”
Section: Literature Review 21 Coverage Of the Issue Of Malalamentioning
confidence: 99%